Theorizing Israel’s occupation: [Book reviews] - Gordon, Neve (Hagar: Studies in Society and Culture, 2006)
Lisa Hajjar, Courting Conflict: The Israeli Military Court System in the West Bank and Gaza (Berkeley, CA: University of California Press, 2005), 312 pp.Yehezkel Lein, Land Grab: Israel’s Settlement Policy in the West Bank (Jerusalem: B’tselem, 2002), 140 pp.James Ron, Frontiers and Ghettos: State Violence in Serbia and Israel (Berkeley, CA: University of California Press, 2003), 262 pp.Rafi Segal and Eyal Weizman (eds.), A Civilian Occupation: The Politics of Israeli Occupation (London: Verso, 2003), 191 pp.